2019
DOI: 10.1159/000503900
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chronic Conditions and Functional Outcome after Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Multiple chronic conditions (MCC) contribute to functional disability in the general population although its role in predicting functional outcome (FO) among patients with stroke is not well understood. There is no universal agreement on the approach to measuring MCC in stroke, and findings have been mixed regarding MCC being an independent predictor for poststroke FO. Objectives: This review aims to summarize the findings of studies that have investigated the relationship between MCC and FO after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…In our study, MCDs status was found to be a risk factor for functional disability. Studies focusing on elderly stroke patients were limited, and we found some similar findings in a population with a single condition (geriatric or stroke) [39]. A recent systematic review of 3339 stroke patients from seven hospital-based cohort studies, indicated that MCDs were longitudinally associated with an 11 % increase in the risk of functional disability after stroke, irrespective of the different methods used for assessing MCDs and functional disability [39].…”
Section: Discussionsupporting
confidence: 62%
“…In our study, MCDs status was found to be a risk factor for functional disability. Studies focusing on elderly stroke patients were limited, and we found some similar findings in a population with a single condition (geriatric or stroke) [39]. A recent systematic review of 3339 stroke patients from seven hospital-based cohort studies, indicated that MCDs were longitudinally associated with an 11 % increase in the risk of functional disability after stroke, irrespective of the different methods used for assessing MCDs and functional disability [39].…”
Section: Discussionsupporting
confidence: 62%
“…Studies focusing on elderly stroke patients were limited, and we found some similar ndings in a population with a single condition (geriatric or stroke) [37]. A recent systematic review of 3339 stroke patients from seven hospital-based cohort studies, indicated that MCDs are longitudinally associated with an 11% increase in the risk of functional disability after stroke, irrespective of the different methods used for assessing MCDs and functional disability [37]. Meanwhile, a large cohort study including a general geriatric population also showed that MCDs signi cantly increased the risk of functional disability by 117% [38].…”
Section: Discussionsupporting
confidence: 54%
“…In our study, MCD status was found to be a risk factor for functional disability. Studies focusing on elderly stroke patients were limited, and we found some similar ndings in a population with a single condition (geriatric or stroke) [37]. A recent systematic review of 3339 stroke patients from seven hospital-based cohort studies, indicated that MCDs are longitudinally associated with an 11% increase in the risk of functional disability after stroke, irrespective of the different methods used for assessing MCDs and functional disability [37].…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies focused predominantly on the prevalence, health care utilization, and health-associated outcomes of multimorbidity among older adults (19)(20)(21)(22). As findings from a study done in China suggest, multimorbidity is more prevalent among the rural population (58.3%) than among their urban counterparts (50.4%) (23).…”
Section: Introductionmentioning
confidence: 99%